2019
DOI: 10.1158/1541-7786.mcr-18-0922
|View full text |Cite
|
Sign up to set email alerts
|

HDAC1 Is a Required Cofactor of CBFβ-SMMHC and a Potential Therapeutic Target in Inversion 16 Acute Myeloid Leukemia

Abstract: Implications: This report describes a novel role for HDAC1 as a cofactor for the leukemogenic fusion protein CBFb-SMMHC and shows that inhibitors of HDAC1 effectively target leukemia cells expressing the fusion protein in vivo.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 51 publications
0
16
1
Order By: Relevance
“…Subsequently, Ro5-3335 has been used to inhibit RUNX1 during a variety of pathophysiological processes including, but not exclusively in, macrophages during septic shock, 165 in retinal angiogenesis 173 and, acute myeloid leukaemia. 183 However, direct binding of Ro5-3335 to CBFβ or RUNX has not been well documented, thus whether Ro5-3335 is a direct inhibitor of Runx remains contentious. 184 …”
Section: Runx1 As a Novel Target In Heart Diseasementioning
confidence: 99%
“…Subsequently, Ro5-3335 has been used to inhibit RUNX1 during a variety of pathophysiological processes including, but not exclusively in, macrophages during septic shock, 165 in retinal angiogenesis 173 and, acute myeloid leukaemia. 183 However, direct binding of Ro5-3335 to CBFβ or RUNX has not been well documented, thus whether Ro5-3335 is a direct inhibitor of Runx remains contentious. 184 …”
Section: Runx1 As a Novel Target In Heart Diseasementioning
confidence: 99%
“…Recent results suggest that HDAC1 is an important component of the AML1/CBFβ-SMMHC fusion complex, which functions to activate transcription of specific target genes. The authors found that in vivo treatment with the HDAC1 inhibitor induced differentiation and apoptosis of leukemia cells, indicating HDAC1 as a potential therapeutic target [59]. These findings suggest an important role for CBFβ-SMMHC in regulating the expression of genes essential for emergence of the hematopoietic stem cell [60].…”
Section: Leukemia Triggered By Cbfβ-myh11mentioning
confidence: 97%
“…For example, HDAC7 regulates the acetylation of H3K27 and the transcriptional activity of super-enhancer-related genes in breast cancer stem cells ( 80 ). A common mutation in AML is a chromosome 16 inversion that fuses the core-binding factor beta (CBFB) gene with the smooth muscle myosin heavy chain gene (MYH11) to form the oncogene CBFB-MYH11 ( 61 ). The expressed protein CBFbeta-SMMHC forms a heterodimer with the key hematopoietic transcription factor RUNX1, and CBFbeta-SMMHC acts together with RUNX1 to activate the transcription of specific target genes ( 61 ).…”
Section: The Components and Process Of Acetylation System In Cancersmentioning
confidence: 99%